(untitled) (Colombia Medica, 2011)
Objective: To determine the effectiveness of pharmaceutical care to improve control of type-2 diabetes mellitus. Methods: We carried out pharmacotherapeutical intervention during 19 months on patients with type-2 diabetes mellitus who were affiliate members of the contributive regime of the General System for Healthcare and Social Security in Bogotá and Cartagena. Through an interview and evaluation of medical records, we obtained information about antidiabetic medications used, doses, other medications, along with Hemoglobin A1c level, arterial pressure, serum low-density lipoprotein cholesterol level, nephropathy screening, retinal screening, foot exams in the last year and problems associated with medication use by means of the DADER method Negative Outcomes Associated with Medication (NOM). Results: The study had a sample of 143 patients (64 intervened and 79 controls) with female predominance (67.1% and 53.1%, respectively), mean age of 63.9±11.2 years. The patients in both groups were taking an average of 6.0±2.7 medications. Initial HbA1c mean was 7.7% and 7.8%, without improvement by the end of the study (7.4% for those intervened and 7.8% for the control group). Hypertension (81.1%) and dyslipidemia (62.9%) were the most important comorbidities. About 50.4% of NOM were of effectiveness, follows 31.3% of necessity. The mean cost per patient in controls was 1.4 greater than for the intervened group. Conclusions: Increased effectiveness of the antidiabetic therapy was not demonstrated in patients intervened with pharmacotherapeutical monitoring, but we did obtain a reduction in healthcare costs.